Design of a switchable microwave absorber - Zhang, Qi (2013)
A novel circuit analog absorber is presented in this letter, which consists of three layers: a complex impedance surface, a dielectric layer containing p-i-n diodes, and a conducting ground plane. The complex impedance surface is a periodic array of unit cells with lumped elements. p-i-n diodes are employed to control the RF signal path to realize different effective thicknesses, which results in different absorbing frequencies. An example is fabricated and tested to demonstrate that the proposed absorber can achieve two switchable operations, one of which covers from 0.85 to 1.88 GHz with a -10-dB reflection coefficient, and the other from 2.66 to 5.23 GHz.